INVERSIONS FAIL TO ACCOUNT FOR ALLOZYME CLINES - Robert A. Voelker; C. Clark Cockerham; F. M. Johnson; Henry E. Schaffer; Terumi Mukai; L. E. Mettler (1978)
ABSTRACT Allozyme and inversion data from natural populations of Drosophila melanogaster from the eastern United States were analyzed to determine whether the clines at allozyme loci are due to nonrandom associations with common cosmopolitan inversions. All inversions show strong clines. Clines were large and significant for half of the eight allozyme loci. An analysis of the contribution of inversions to clines of allozyme genes revealed three outcomes: the inversion cline (1) enhanced the allozyme cline, but was only partly responsible, (2) reduced the allozyme cline, and (3) had no effect. The allozyme clines were mainly determined by the pattern of allele frequencies within the chromosomal arrangements. Consequently, it was concluded that allozyme clines would exist in the absence of inversion clines.